PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, BEBAN KERJA, DAN KOMUNIKASI ORGANISASI TERHADAP KINERJA KARYAWAN DI PT MARSUDI UTOMO SEJAHTERA KOTA SURABAYA - Ade Dewa Narendra; Sri Budi Kasiyati (CV. ADIBA AISHA AMIRA, 2026)
The development of the culinary industry in Surabaya has driven increased competition among business players, including PT Marsudi Utomo Sejahtera as the manager of the Ayam Bakar Pak D brand. Initial observations indicate dynamics in aspects of transformational leadership style, workload, and organizational communication, which are suspected to influence employee performance levels. This study aims to analyze the effect of transformational leadership style, workload, and organizational communication, both partially and simultaneously, on employee performance at PT Marsudi Utomo Sejahtera Surabaya. This research uses a quantitative method with a questionnaire instrument based on a Likert scale, and the data obtained are processed using SPSS 25. The research sample consisted of 78 employees, selected using a saturated sampling technique because the entire population was made respondents. Testing includes validity tests, reliability tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination (R²). The results of the study indicate that transformational leadership style has a significant influence on employee performance. Meanwhile, workload has an influence, but it is not significant, so that increasing or decreasing workload does not have a significant impact on performance. On the other hand, organizational communication was recorded as having a significant partial influence on employee performance. Furthermore, all three variables still have a significant influence when tested simultaneously. This finding confirms that inspiring leadership and effective internal communication are the main drivers of performance improvement, while workload management requires attention, although it did not show a strong influence in this study.